Expanded application of wearable cardioverter defibrillators beyond current guidelines: proposal for a European register explained through single clinical scenarios. - Buia, Veronica; Ciotola, Francesco; Bastian, Dirk; Stangl, Dorina; Walascheck, Janusch; Rittger, Harald; Vitali-Serdoz, Laura (Open Heart, 2024)
The wearable cardioverter defibrillator (WCD) is becoming a more and more widely used instrument for the prevention of sudden cardiac death of patients either with a secondary prevention implantable cardioverter defibrillator indication or with a transient high risk of sudden cardiac death. Although clinical practice has demonstrated a benefit of protecting patients for a period as long as 3-6 months with such devices, the current European guidelines concerning ventricular arrhythmias and sudden cardiac death are still extremely restrictive in the patient selection in part because of the costs derived from such a prevention device, in part because of the lack of robust randomised trials.To illustrate expanded use cases for the WCD, four real-life clinical cases are presented where patients received the device slightly outside the established guidelines. These cases demonstrate the broader utility of WCDs in situations involving acute myocarditis, thyrotoxicosis, pre-excited atrial fibrillation and awaiting staging/prognosis of a lung tumour. The findings prompt expansion of the existing guidelines for WCD use to efficiently protect more patients whose risk of arrhythmic cardiac death is transient or uncertain. This could be achieved by establishing a European register of the patients who receive a WCD for further analysis.
EVALuna2:589212